(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the growth and quality of Schizolobium amazonicum seedlings (Huber ex Ducke) under pre-germinative seed treatment and foliar application of chemical agents during formation. The experiment was carried out in the seed analysis laboratory and vegetation house at the Universidade Estadual de Mato Grosso do Sul/Unidade Universitária de Cassilândia -MS. A completely randomized design was used, in a 2x3 factorial scheme, consisting of two pre-germinative treatments for seed hydration (ST1 - water and ST2 - 0.2% calcium nitrate) and three chemical agents supplied via leaf (FT1 - control without treatment, FT2 - Biostimulant composed of 0.1% gibberellin + 0.2% auxin + 0.2% calcium nitrate and FT3 - mixture containing 0.01% paclobutrazol + 0.2% urea) with 10 replicates per treatment and 6 plants per repetition. At 45 days the first measurements were made and the final evaluation was made at 60 days (planting period of seedlings in the field). The treatment of seeds with calcium nitrate produced seedlings with similar quality to seedlings originated from seeds that were hydrated only with water. The use of paclobutrazol and nitrogen in foliar application resulted in seedlings of high quality of Schizolobium amazonicum.